2015
DOI: 10.1080/08870446.2015.1082561
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits and body mass index: Modifiers and mechanisms

Abstract: Objective To identify how demographic factors (sex, age, ethnicity) modify the association between personality traits and body mass index (BMI) and to test the extent that diet and physical activity account for the personality-BMI relations. Design Cross-sectional study with a diverse sample (N=5,150, 50% female, 19% African American, 15% Hispanic). Participants completed a measure of the five major dimensions of personality and reported on their physical activity, diet and food intake behavior, and height a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
114
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(130 citation statements)
references
References 39 publications
13
114
2
1
Order By: Relevance
“…However, it needs to be emphasised that no statistically significant correlation between neuroticism and conscientiousness on the one hand and effective weight loss and change of DASH values on the other hand was found, which is contrary to the findings of other authors [6, 10, 11, 13-15]. Nevertheless, the positive changes of DASH values and weight loss were observed.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…However, it needs to be emphasised that no statistically significant correlation between neuroticism and conscientiousness on the one hand and effective weight loss and change of DASH values on the other hand was found, which is contrary to the findings of other authors [6, 10, 11, 13-15]. Nevertheless, the positive changes of DASH values and weight loss were observed.…”
Section: Discussioncontrasting
confidence: 56%
“…It should be noted that a combination of a high level of conscientiousness and a low level of neuroticism has been widely discussed in the literature. Meta-analyses showed that these 2 traits played a key role in effectiveness of treatment for weight loss [6, 10, 11, 13-15]. The study carried out among 235 persons with obesity demonstrated that the intensity of neuroticism was associated with the more frequent occurrence of inappropriate eating behaviours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these traits, the most studied personality dimension in health research is neuroticism, and there is robust evidence of associations between this personality dimension and a wide range of both mental and physical health problems including depression, anxiety, eating disorders, cardiovascular disease, and type 2 diabetes [10]. In addition, several studies have observed elevated scores of neuroticism in individuals with obesity from the general population [8,11,12], suggesting a positive association between neuroticism and BMI. In addition, both obese and underweight individuals tend to report more psychiatric symptoms than normal-weight individuals [13], indicating that these weight groups may score higher on neuroticism [10].…”
Section: Introductionmentioning
confidence: 99%